1997
DOI: 10.1111/j.1151-2916.1997.tb02913.x
|View full text |Cite
|
Sign up to set email alerts
|

Protons and Deuterons in Magnesium‐Doped Sapphire Crystals

Abstract: The OH‐ and OD‐ stretching frequencies in magnesium‐doped aluminum oxide crystals were determined by infrared absorption measurements. Two very broad bands centered at }3005 and 2228 cm‐1 were observed for OH‐ and OD‐, respectively. Polarization experiment results were compatible with OH‐ (OD‐) ions lying in the basal plane, as is the case in undoped crystals. The threshold temperature for the in‐diffusion of deuterons was obtained by annealing the samples in flowing D2O vapor; the resulting value was }1050 K.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 31 publications
3
15
0
Order By: Relevance
“…Although the band observed at 3010 cm −1 in the Mgdoped samples (Volynets et al, 1972;Ramírez et al, 1997b) is significantly broader than those observed in Ti-or V-doped samples, the models of interstitial protons associated with substituted Mg 2+ ions are consistent with experimental observation in terms of polarization properties and frequencies ( Table 2). The theoretical I z /I x ratio of the models (Table 2) ranges between 2.88 and 4.99, which compares favorably with the 3.33 ratio reported by Volynets et al (1972) and with the 5 : 1 ratio reported for the similar bands observed in Nior Co-doped samples (Eigenmann and Günthard, 1971).…”
Section: Interpretation Of the Experimental Spectra Of Doped Corundumsupporting
confidence: 83%
See 1 more Smart Citation
“…Although the band observed at 3010 cm −1 in the Mgdoped samples (Volynets et al, 1972;Ramírez et al, 1997b) is significantly broader than those observed in Ti-or V-doped samples, the models of interstitial protons associated with substituted Mg 2+ ions are consistent with experimental observation in terms of polarization properties and frequencies ( Table 2). The theoretical I z /I x ratio of the models (Table 2) ranges between 2.88 and 4.99, which compares favorably with the 3.33 ratio reported by Volynets et al (1972) and with the 5 : 1 ratio reported for the similar bands observed in Nior Co-doped samples (Eigenmann and Günthard, 1971).…”
Section: Interpretation Of the Experimental Spectra Of Doped Corundumsupporting
confidence: 83%
“…The relative intensity of the OH-stretching bands in Ti-and V-doped samples experimentally treated at high temperature (1400 K) depends on their cooling rate (Ramírez et al, 2004), which is consistent with the record of a temperature-dependent distribution of OH defects displaying different clustering schemes. In addition, a broader band extending from 2900 to 3100 cm −1 with a dominant polarization in the direction perpendicular to the (001) plane is observed in Mg-doped samples (Volynets et al, 1972;Ramírez et al, 1997b). Broad bands with similar properties have been reported at 3025 and 2972 cm −1 in Coand Ni-doped samples, respectively (Eigenmann and Günthard, 1971).…”
Section: Introductionsupporting
confidence: 62%
“…Thus, it is likely that hydrogen impurity could be a “hidden” source, which drastically transforms the non-conductive β-Ga 2 O 3 to an n-type conductor. Note that hydrogen in oxides can present itself in different forms and have different charge states [ 50 , 51 , 52 , 53 , 54 ], which, in principle, complicates the overall picture for understanding.…”
Section: Resultsmentioning
confidence: 99%
“…29,30 Their presence tends to decrease the surface energy of the basal plane. 29,31 It has also been noted that anisotropic grain growth is observed at high temperature near alumina surfaces in Ar/H 2 O environment. 32 This anisotropy is associated with the development of basal GB planes.…”
Section: (1) Overall Microstructural Featuresmentioning
confidence: 99%